Riches and Poverty (1910) - Money, L. G. Chiozza (Leo George Chiozza), 1870-1944 (Salt Lake City, UT : Project Gutenberg, 2021)
"Riches and Poverty" by L. G. Chiozza Money is a socio-economic analysis written in the early 20th century. The work examines the distribution of wealth and income in Britain, highlighting the growing disparity between the rich and the poor during a time of social unrest. The author delves into the statistics of British incomes around 1908-1909, arguing that despite the overall wealth of the nation, significant portions of the population are living in poverty. The opening of the book sets the stage for a thorough exploration of economic inequality in Britain. It begins with a note on the methodology and statistics used, presenting stark figures that indicate a concentrated wealth distribution, where a small number of individuals hold a large share of the national income. This is contrasted with the plight of the vast majority, many of whom struggle to meet basic needs. The author emphasizes the disconnect between the apparent prosperity of the nation and the real living conditions of its poorest citizens, laying the groundwork for a critique of current economic policies and inviting a reevaluation of how wealth is distributed and understood in society. (This is an automatically generated summary.)
Book I. The error of distribution: Thoughts arising out of a great controversy. The national income. Distribution of the national income. The estates of rich and poor. The national accumulations. The monopoly of capital. The area of the United Kingdom. Those who work and those who wait. Profits, bad trade and unemployment. Part of their wages. Consequences. The waste of capital -- Book II. Towards organization: The golden key. The nation's children. The school. The home. The empty country. Organization. The aged poor. Adam Smith's first maxim of taxation. The main instrument of taxation. The death duties. Of revenue without taxation. Conclusion.
Release date is 2021-02-23
Turgut Dincer, Chris Pinfield and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Great Britain -- Economic conditions -- 19th century; Working class -- Great Britain -- History; Finance -- Great Britain -- History; Poor -- Great Britain -- History